Subarachnoid haemorrhage from the rupture of two intracranial aneurysms in the same day: a rare occurrence, not a myth. (16th February 2016) - Dubois, Jerome Laval Cyril; Major, Otto
Abstract : The incidence of intracranial aneurysms is approximately 6% throughout the world, although it can be more prevalent in some populations than others. Subarachnoid haemorrhage from a single aneurysm rupture can be devastating, with approximately 35% of patients not regaining consciousness after the initial bleed. In some cases, patients will have two or more aneurysms at presentation, and only one of them will have bled. Having two or more aneurysms that have bled within a few minutes or few hours of one another, is almost unheard of. Our case report is based on a patient who presented with subarachnoid haemorrhage from two ruptured aneurysms, confirmed intraoperatively and corroborated by the available, preoperative, standard head CT scan, which can be performed in any hospital with CT scanning facilities, and CT angiogram.